A Yank discovers Australia - Master-Sarg. (Sydney : Currawong Publishing Co., 1945)
"Australia, land of wonders, seen through the eyes of an American soldier writing home to the folk" - note from Currawong advertisement, Book News, August 1945. But actually written by Australian J.W. Heming, who published some 50 pulp novelettes in different genres and under a variety of names and pseudonyms. Includes observations comparing Aboriginal Australians with North American Indians.
Keywords: Animals - Mammals - Marsupials - Koalas; Animals - Mammals - Dingoes / Dogs; Indigenous peoples - North America - Cree; Hunting - Crocodile; Race relations - Racism - Stereotyping; Animals - Birds - Eagles / Hawks / Crows; Race relations - Attitudes; Animals - Birds - Kookaburras / Kingfishers; Australia -- Description and travel -- 1901-1950.; Australia